Aerobic Physical Activity and Depression Among Patients With Cancer - Giovanni, Giovanni; Michelle, Michelle (International Medical Journal Corp. Ltd, 2024)
Background: The literature presents a compelling case for the role of aerobic physical activity in alleviating depressive symptoms among cancer patients, particularly breast cancer survivors. The foundational analysis by (D Patsou et al., 2017) underscores the prevalence of depression in breast cancer survivorship, with rates ranging from 1.5% to 46%, and emphasizes the potential of physical activity as a non-pharmacological intervention. Their meta-analysis reveals that regular exercise can mitigate treatment-related side effects and improve survival outcomes, although they caution against the non-uniform reporting of exercise interventions, which complicates the interpretation of optimal exercise regimens ((D Patsou et al., 2017)). Literature Review: Building on this foundation, the critical analysis by (Marconcin et al., 2022) reinforces the efficacy of supervised aerobic exercise, noting that structured programs yield better psychological outcomes compared to unsupervised activities. Their findings highlight the importance of the exercise environment, suggesting that social interactions and professional guidance enhance adherence and motivation, which are crucial for effective mental health interventions in this population ((Marconcin et al., 2022)). Conclusion: In conclusion, the synthesis of these studies indicates that aerobic physical activity is a critical component in managing depression among cancer patients, particularly breast cancer survivors. While challenges remain regarding the standardization of exercise protocols and the need for tailored interventions, the integration of structured physical activity into treatment plans holds significant promise for enhancing the psychological well-being of cancer survivors. Future research should focus on addressing methodological limitations and exploring individualized exercise regimens to optimize mental health outcomes in this vulnerable population.